Trauma, experiences of sexual violence and mental health in LGBTIQ+ refugees seeking psychosocial support in Germany - Yuriy Nesterko; Kim Schönenberg; Anna Weißig; Tatiana Kulbakina; Heide Glaesmer (Epidemiology and Psychiatric Sciences)
Abstract Aims Only little empirical evidence exists on mental health in LGBTIQ+ refugees. In the present study, trauma exposure, experiences of sexual violence and current treatment needs for physical and mental health were investigated in association with symptoms of anxiety, depression, post-traumatic stress disorder (PTSD) and somatic symptom burden in LGBTIQ+ asylum-seekers resettled in Germany and seeking psychosocial support.